Enūma eliš I and the issue of 'unobtrusive variants' - Worthington, Martin (Hamburger Studien zu Gesellschaften und Kulturen der Vormoderne, 2025)
This paper uses the two most recent paper editions of the first Tablet (chapter) of the Babylonian poem Enūma eliš to investigate the significance of unobtrusive variants, i.e. the sort which tend to be ignored by editors. With detailed analysis of manuscripts’ morphology, it shows that there are more meaningful variants, and more important ones, than is generally recognized. There also seem to be differences between Assyrian and Babylonian manuscripts, probably reflecting the circumstance that the poem’s protagonist, Marduk, was a Babylonian (and not Assyrian) god.
[book in series "Hamburger Studien zu Gesellschaften und Kulturen der Vormoderne"]
Keywords: assyriology, variants, textual history, Enuma elish; Manuscript, Book and Print Cultures; Assyriology; manuscript variants; textual criticism